Pemberian Nafkah Anak Akibat Putusnya Perkawinan karena Perceraian di Desa Permis Kecamatan Simpang Rimba Kabupaten Bangka Selatan - Adi Saputra; Darmiko Suhendra; Imam Alfikri Pratama (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2023)
Child support problems arise after divorce. Parents often neglect and ignore their rights and obligations, even though their obligations to care for, educate and support their children are no different from when they were not divorced. This research is about providing child support due to the breakdown of marriage due to divorce in Permis Village, Simpang Rimba District, South Bangka Regency with the problem of how to provide child support after divorce in the Permis Village Community, Simpang Rimba District, South Bangka Regency and the influencing factors. This research aims to describe the provision of child support in the Permis Village community, Simpang Rimba District, South Bangka Regency, whether its implementation is in accordance with the applicable regulations or not. This research shows that the mother generally provides child support after divorce in the Permis Village community, while ex-husbands do not fully or only partially and some even do not provide child support rights at all, which results in child support rights not being fulfilled properly. Providing child support in the Permis Village community is not in line with the rules as contained in Article 41 of the Marriage Law. The influencing factors are the ex-husband who is irresponsible in fulfilling the child's child support rights after divorce, the ex-husband's economic limitations and the ability of the working mother to provide for the child. This research suggests that a working father should try to provide support for his children after divorce according to his ability. For husbands and wives who are going to divorce, it is necessary to know first about children's maintenance rights after divorce so that children do not become victims of divorce due to failure to fulfill child maintenance properly after divorce, and for future researchers to be able to conduct more in-depth research so that they can provide better results and provide positive contribution to the child's future after divorce.